Strategi Meningkatkan Motivasi Belajar Ekonomi: Komunikasi Guru, Reward dan Ice Breaking - Sabrina, Amsya; Nafiati, Dewi Amaliah; Fr., Dewi Apriani; Habibi, Dewi Beni (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study investigates the influence of teacher communication style, reward provision, and the implementation of ice breaking activities on students’ motivation in learning economics. The research was motivated by the observed low enthusiasm and engagement of students during economics lessons at SMA N 1 Balapulang.Method – The research employed a quantitative approach with a correlational associative survey design. Data were collected through a validated questionnaire comprising 60 Likert-scale items, administered to a sample of 40 grade XI students selected using proportionate stratified random sampling. Additional data were obtained from observation and documentation. The data were analyzed using descriptive statistics, simple linear regression, and multiple linear regression with the aid of SPSS version 26. Findings – The results indicate that teacher communication style and ice breaking activities significantly and positively affect students’ learning motivation, while reward provision shows no significant effect. Simultaneously, the three variables contribute significantly, explaining 33.8% of the variance in learning motivation. Teacher communication style was found to have the strongest relative influence, followed by ice breaking, whereas rewards had a weak and non-significant contribution. Research Implications – These findings highlight the importance of interpersonal communication and engaging classroom dynamics in enhancing students’ learning motivation, particularly in subjects often considered less appealing such as economics. Teachers are encouraged to strengthen their communication skills and incorporate creative ice breaking strategies, while the use of rewards should be reconsidered to align better with students’ needs and perceptions. Future studies may expand the scope by including intrinsic motivation factors, family environment, or technology-based learning methods.